2013
DOI: 10.1002/cncr.28144
|View full text |Cite
|
Sign up to set email alerts
|

Pronecrotic mixed lineage kinase domain‐like protein expression is a prognostic biomarker in patients with early‐stage resected pancreatic adenocarcinoma

Abstract: Background Mixed lineage kinase domain-like protein (MLKL) is a necrosome component mediating programmed necrosis that may be an important determinant of cancer cell death. The goal of the current study was to evaluate the prognostic value of MLKL expression in patients with pancreatic adenocarcinoma (PAC). Methods Tissue from 80 patients was collected from a prospectively maintained database of patients with PAC who underwent pancreaticoduodenectomy between January 2000 and October 2008. Immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 30 publications
4
77
2
Order By: Relevance
“…They found that 24 of 35 studies 17 (67%) with a Kaplan-Meier estimate were susceptible to competing risk bias. This estimate is 18 higher than ours likely because they excluded studies in which all-cause mortality was the only 19 outcome. Our study also found that competing risk bias was widely prevalent in the published 20 medical literature.…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…They found that 24 of 35 studies 17 (67%) with a Kaplan-Meier estimate were susceptible to competing risk bias. This estimate is 18 higher than ours likely because they excluded studies in which all-cause mortality was the only 19 outcome. Our study also found that competing risk bias was widely prevalent in the published 20 medical literature.…”
Section: Resultscontrasting
confidence: 75%
“…al. [5] 16 While researchers, reviewers, and editors are familiar with Kaplan-Meier curves, the 17 susceptibility of such analyses to biased estimates when competing events are present (what we 18 term 'competing risk bias') may be less well known. We designed this study to determine the 19 prevalence of competing risk bias in Kaplan-Meier analyses in studies published in prominent 20 medical journals and the potential magnitude of over-estimated risks caused by competing risk 21 bias.…”
mentioning
confidence: 98%
“…Thus, MLKL provides a further evidence that a necroptosis protein has prognostic value in patients with cancer, which found prognostic evidence in patients with pancreatic adenocarcinoma and ovarian cancer. 12,13 One possible potential mechanism for the association of low MLKL expression with poor prognosis in patients with colon cancer may be a result of decreased necroptosis signaling in these patients, which suggests that necroptosis is an important determinant of cancer cell death and outcome in patients with colon cancer. It is unclear whether the administration of adjuvant chemotherapy improves the survival in patients with stage II colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10]11 Interestingly, recent studies suggested that MLKL expression can serve as a potential prognostic biomarker for patients with pancreatic and ovarian cancer. 12,13 However, the role of MLKL proteins in cancer cell death procedure and the prognostic value of MLKL in colon cancer are unknown. In this study, we try to investigate the prognosis value of MLKL expression in patients with colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…RIP3 expression in the hematopoietic system may limit cancer invasion and metastasis. Likewise, reduced MLKL expression is significantly associated with decreased overall survival in gastric, ovarian, cervix, colon, and pancreatic cancers [33][34][35][36][37]. Thus, RIP3 and MLKL expression could potentially serve as prognostic biomarkers for these cancers.…”
Section: The Implications Of Programmed Necrosis For Cancer Therapymentioning
confidence: 99%